Investigation on Low Power for Reducing Counter Delay Digital Circuit Using 45nm Technology - S.Mohamed Sulaiman, Mr.; B.Jaison, Dr.; M.Anto Bennet, Dr.; Purushoth, S.; Jawahar, R.; Suriya, T. (International Journal of Engineering and Technology, 2018)
The counter circuit is a basic component in floating point operation. The main aim is to speed up the operation of the circuit. The new derived Boolean function which is designed by the concept of transmission gate logic in order to reduce the number of gates and speed the circuit operation. By the transmission gate logic the 8 bit counter circuit is designed. Moreover, 16 bit and 32 bit circuit is designed using 45 nm technology. The result of 16 and 32bit circuits are better than the reported design and by comparison, proposed design is faster and the delay of the circuit is minimized when compared to the reported design.